2019
DOI: 10.1016/j.molcel.2019.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Spt5-Pol II by Small-Molecule Inhibitors Uncouples Distinct Activities and Reveals Additional Regulatory Roles

Abstract: Highlights d Discovery of Spt5-Pol II small-molecule inhibitors (SPIs) that mimic Spt5 knockdown d SPIs relieve promoter-proximal pausing and inhibit inflammatory gene activation d SPIs inhibit mutant huntingtin gene transcription and 3 0 end processing of histone genes d Selective targeting of Spt5-Pol II activities by SPIs uncouples its different functions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 65 publications
4
28
0
Order By: Relevance
“…These overall trends were also observed within PI distributions when we extended this analysis to publicly available data ( Supplemental Fig. 12 ).While the PI is known to depend on the method used to define the paused region [ 15 , 24 ], we found that the trends across protocols remained consistent even with different pause windows and read counting software ( Supplemental Fig. 16 ).…”
Section: Resultssupporting
confidence: 57%
“…These overall trends were also observed within PI distributions when we extended this analysis to publicly available data ( Supplemental Fig. 12 ).While the PI is known to depend on the method used to define the paused region [ 15 , 24 ], we found that the trends across protocols remained consistent even with different pause windows and read counting software ( Supplemental Fig. 16 ).…”
Section: Resultssupporting
confidence: 57%
“…This enabled to identify withaferin A, a previously characterised molecule with anti-inflammatory and anticancer activities, as allosteric inhibitor of NF-κB dimerisation. In another study, ∼100 000 pure natural plant molecules were screened to identify inhibitors of Spt5, a disease-associated transcription elongation factor that directly interacts with Rpb1, the large subunit of RNA polymerase II [ 81 ]. The authors identified several compounds that interfere with Spt5/Rpb1 PCA signal and Spt5 functions in cells.…”
Section: Pcas Applied To Large-scale Analysis Of Ppismentioning
confidence: 99%
“…As Supt4h and Supt5h are needed for normal functioning of mammalian cells, extensive knockdown can result in broad effects on cellular RNA synthesis ( 53 ), whereas partial knockdown is associated with limited changes in RNAPII-S2 template occupancy and RNA synthesis (Figures 1 and 5 ; see also ( 16 , 18 , 39 )). As introns were included in our calculations of G + C content, and total gene length and G + C content are determined largely by sequences present in introns ( 54 ), intronic sequences, which are less conserved among species than exonic sequences ( 55 ) substantially affect the template occupancy we have reported.…”
Section: Discussionmentioning
confidence: 99%